Practice Recommendations for Risk-Adapted Head and Neck Cancer Radiation Therapy During the COVID-19 Pandemic: An ASTRO-ESTRO Consensus Statement - Thomson, David J.; Palma, David; Guckenberger, Matthias; Balermpas, Panagiotis; Beitler, Jonathan J.; Blanchard, Pierre; Brizel, David; Budach, Wilfred; Caudell, Jimmy; Corry, June; Corvo, Renzo; Evans, Mererid; et al. (International journal of radiation oncology, biology, physics, 2020)
Because of the unprecedented disruption of health care services caused by the COVID-19 pandemic, the American Society of Radiation Oncology (ASTRO) and the European Society for Radiotherapy and Oncology (ESTRO) identified an urgent need to issue practice recommendations for radiation oncologists treating head and neck cancer (HNC) in a time of limited resources and heightened risk for patients and staff. A panel of international experts from ASTRO, ESTRO, and select Asia-Pacific countries completed a modified rapid Delphi process. Topics and questions were presented to the group, and subsequent questions were developed from iterative feedback. Each survey was open online for 24 hours, and successive rounds started within 24 hours of the previous round. The chosen cutoffs for strong agreement (≥80%) and agreement (≥66%) were extrapolated from the RAND methodology. Two pandemic scenarios, early (risk mitigation) and late (severely reduced radiation therapy resources), were evaluated. The panel developed treatment recommendations for 5 HNC cases. In total, 29 of 31 of those invited (94%) accepted, and after a replacement 30 of 30 completed all 3 surveys (100% response rate). There was agreement or strong agreement across a number of practice areas, including treatment prioritization, whether to delay initiation or interrupt radiation therapy for intercurrent SARS-CoV-2 infection, approaches to treatment (radiation dose-fractionation schedules and use of chemotherapy in each pandemic scenario), management of surgical cases in event of operating room closures, and recommended adjustments to outpatient clinic appointments and supportive care. This urgent practice recommendation was issued in the knowledge of the very difficult circumstances in which our patients find themselves at present, navigating strained health care systems functioning with limited resources and at heightened risk to their health during the COVID-19 pandemic. The aim of this consensus statement is to ensure high-quality HNC treatments continue, to save lives and for symptomatic benefit.